CORRECTION AND COMPENSATION ROLE OF RECREATION IN LIVING AND WORKING CONDITIONS OF A MODERN MAN - Budimir Bijelić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Nowadays, living and working conditions have reduced a modern man s motion and power activities in leisure and operating circumstances. Beside the dominant hypokinezis, there are many other factors which have negative infl uence on biological structure and health status of a modern man. Correction and compensation of the functions disturbed as well as a body structure can be performed effi ciently on a healthy basis only with adequate training programs. The training process is particularly effi cient when it is being performed under the direct infl uence of natural factors such as sun, fresh air and water.